APPLICATION OF THE ULTIMUM REMEDIUM PRINCIPLE TO THE CHILDREN INVOLVED IN NARCOTIC - Syachdin, Syachdin (Tadulako University, 2016)
The focus of this study is the existence of legal principles applicable to the child ultimum remedium the doers. The issues concerning the application of the principle of ultimum How remedium against children as perpetrators Crime Narcotics. Studies conducted an empirical study aims to determine the juridical form of the application of the principle of ultimum remedium in narcotic crime committed by a child. Law Number 11 Year 2012 on Juvenile Justice System and Law Number 35 Year 2009 on Narcotics have to give freedom to the judge to apply the principle of ultimum remedium. However, the application of the principle of ultimum remedium still needs to be studied more in practice. Lack of innovation sanctions given by the judge against children as a criminal narcotics makes imprisonment remains a potent drug (by judges) in the system of juvenile justice, so that the principle of ultimum remedium that should be mandated by an Act of Justice System Child and the Law on Narcotics only limited without a popular mandate fulfilled.